(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
This article analyzes the issue of effective training of insurance terms through new pedagogical technologies. Due to the fact that the insurance industry covers complex concepts, it is important to understand the content of their content and apply in practice. In this regard, the methods of innovative educational techniques, including the use of interactive methods, information and communication technologies, problematic education and game methods play an important role in the improvement of insurance terms.